Visitors' engagement and authenticity: Japanese heritage consumption. (February 2015) - Bryce, Derek; Curran, Ross; O'Gorman, Kevin; Taheri, Babak
Abstract: Understanding the sense of authenticity of heritage attractions is important for tourism management and marketing because presentation, interpretation and verification has a direct bearing on motivations to visit and engage with heritage tourism sites. This paper establishes relationships among the concepts of culturally specific motivation, perception of authenticity, engagement and attendant behavioral consequences based on domestic visitors' experiences at Japanese heritage sites. It further extends Kolar and Zabkar's (2010) model of authenticity by including concepts of serious leisure, heritage related behaviors, self-connection and their effects over engagement using Partial Least Square, whereby both formative and reflective scales are included. The structural model is tested with a sample of 768 visitors in a culturally specific setting of Japanese heritage sites. The empirical validation of the conceptual model supports the research hypotheses. These findings contribute to a better understanding of visitors' perceptions and valuation of authenticity in Japanese tourist attractions. Several implications can be drawn from the study findings and interesting directions for future research are provided. Highlights: Tests a structural model (PLS) using both formative and reflective scales. Integrating/introducing a visitors' engagement concept to authenticity. Focuses on Japanese visitors' experience of authenticity. Concepts: serious leisure, heritage behaviors, self-connection and engagement. Objective authenticity and engagement centric model presented.